84 and 86 Charles Street, January 14, 1973 - Waid, C. Franklin (Tufts Archival Research Center, 2005)
Street-level view of 84, 86 and 88 Charles Street, located between Mount Vernon Street to the south and Pinckney Street to the north. A street lamp decorated with garland and a parking meter are located on the sidewalk in front of the buildings. A large clock hangs from the window pane at 88 Charles Street. 7 3/8 x 9 3/8, 7 7/8 x 9 7/8 overall Photographs